Теоретичні розробки «празького тексту» у творчості Даніели Годрової - Польова, Ю. (Літературознавчі обрії. Праці молодих учених, 2010)
The article is concerned with the category analysis of «the Prague text» in the theoretical research and literary works by modern Czech writer Daniela Hodrova. In her works the urban space is considered to be a special kind of text. At the same time the city acts as a complicated semiotic object able to generate literary «city texts» about itself.